Problems and Solution Proposals Related to Sheep and Goat Husbandry in Kastamonu Province - Hacer Tüfekci; Mustafa Olfaz (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted by using a survey made at 80 enterprises from 63 villages with the aim of determining situations, problems and solution proposals related to the sheep and goat farms in Kastamonu province. The average age of the farmers was 49.3 years. The farmers were 8.75% of primary school graduates, 68.75% of secondary school and also 22.6% of illiterate. The enterprises have raised animals as 31.75% of state + own land and 68.75%’ of private + leased land. Also they are kept the rate of 70% Hair goat, 30% Angora goat and 55% Merino sheep, 42.5% Akkaraman sheep, and 16.25% Turkmen genotype, 7.5% Sakız sheep and 6.25% of Kıvırcık Sheep. The average flock sizes goat and sheep enterprises were 77.3 head goats and 71.7 heads sheep, respectively. Sixty percent of the breeder feed their animals on the pasture for 8-10 months and only 30% the breeders give supplementary feeding before and during mating period. The enterprises have 31.2% parturition chamber and 92.5% lamb growth areas. While all enterprises are routinely used to protective vaccines but only used disinfectant of 73.7% enterprises. The reason of sheep and goat breeders is majority contributions of income and habits. So, flock sizes are small (74.5 heads animal). In conclusion, young people by encouraging small animal farming in the province of Kastamonu, should be given to technical, economic support and educational seminars. In the future, as the sole source of income and a large flock size may lead to a development of sheep and goat breeding in Kastamonu province.